Diversity of chemistry, activities, and depths zone of new compounds isolated from marine-sediment fungi - Safwan Safwan, Siti Rahmatul Aini, Sucilawaty Ridwan, Anna Pradiningsih, Eskarani Tri Pratiwi, Abdul Rahman Wahid (Journal of Applied Pharmaceutical Science, 2024)
Marine sediments are one of the great habitats of microbial and awareness about their diversity and purpose is relatively limited. One of the major and ubiquitous members of marine sediments-inhabiting microorganisms is fungi. Marine-sediment fungi are an important source of metabolites in drug discovery for promise as therapeutic agents. Marine-sediment fungi lean to yield structurally typical and biologically active secondary metabolites which have been recorded in current years. The fungi from marine sediment habitats have increased interest and appear an important part of drug discovery. The fungi from marine sediment have been found at depths ranging from rom the shallowest (less than 200 meters) to the deepest or abyssopelagic zone (4,000 – 6,000 meters). Fungi growth in extreme environments at depths more than 1,000 meters produces typical natural products for entrenchment and communication, which promise as therapeutic agents. This review report focusing on the diversity of structures and activity of new compounds isolated marine-sediment fungi at depths ranging, covering the literature from 2017 to 2022.
Keywords: Marine-derived fungus, marine-sediment fungi, marine fungi, natural products, bioactivities